Plan de negocios para la implantación de un centro integral de diabetes en la ciudad de Loja - Celi García, Gina Daniela (2013)
The main purpose of this project is to design a business plan for the implementation of a Diabetes Center in Loja. Currently, Diabetes patients who live in Loja lack the services and care that a diabetes center could provide to them. With this in mind, a micro and macro analysis has been established to determine the functional business aspects of building a Diabetes Center in Loja. VIDABETES is a center that provides specialized medical care that is comprised on the prevention, diagnosis, treatment, psychological support, follow-up and control, and the professional service of nurses to patients. This is achieved by having top class doctors in each of the principal branches that are required by a diabetic patient. After completing the macro analysis for the diabetic center, it was determined that this project results to be attractive. This is due to the fact that in recent years Ecuador has been investing more funds in the social, personal and community care industry. After conducting a marketing research survey to diabetic people in Loja, it was concluded that 95 percent of the surveyed people feel that a specialized diabetic center would be very convenient to them. This signifies a large business opportunity and it also poses an attractive competitive advantage since VIDABETES would not have a direct competitor in Loja. Once the marketing analysis was completed, the business segment goals were formulated and the marketing plan was established to manage the different strategies and objectives that enable the business goal’s to be attainable. A financial plan was also developed with the purpose of showing the necessary resources needed to accomplish the business plan and consequently to determine if the project will be financially successful or unsuccessful. The necessary investment for the business is USD102.090and it will base on 2 forms of financing which will include internal resources and external financing. The primary sources of income for the Diabetes Center will take place by selling specialized medical bundles, providing private medical appointments, and allowing patients to have access to the center’s gym at all times. Furthermore, the sales forecast is given for the first 5 years of operation for VIDABETES. Once the financial analysis was finalized, it was concluded that the business would be profitable. It was determined that the business will have an Internal rate of return (IRR) of 81.90% and a Net present value (NPV) of USD 89.548,31.